2017
DOI: 10.1042/ebc20160079
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical approaches to [NiFe] hydrogenase

Abstract: The mechanism by which [NiFe] hydrogenase catalyzes the oxidation of molecular hydrogen is a significant yet challenging topic in bioinorganic chemistry. With far-reaching applications in renewable energy and carbon mitigation, significant effort has been invested in the study of these complexes. In particular, computational approaches offer a unique perspective on how this enzyme functions at an electronic and atomistic level. In this article, we discuss state-of-the art quantum chemical methods and how they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 190 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…62,63 This line of research has allowed for accurate rate constant prediction for molecule-surface reactions 64 , while Piccini et al showed how energy barriers for large systems like zeolites (over 1000 atoms) could be calculated within chemical accuracy (within 4 kJ/mol) using Density Functional Theory (DFT) methods. 65 But there are still significant difficulties for metal catalysts, for example metalloenzymes, where there may be multiple reactive sites requiring a QM description 66 , and for which errors in relative free energies do not generally fall below 20 kJ/mol due to poor accounting of strong correlation using DFT 67 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…62,63 This line of research has allowed for accurate rate constant prediction for molecule-surface reactions 64 , while Piccini et al showed how energy barriers for large systems like zeolites (over 1000 atoms) could be calculated within chemical accuracy (within 4 kJ/mol) using Density Functional Theory (DFT) methods. 65 But there are still significant difficulties for metal catalysts, for example metalloenzymes, where there may be multiple reactive sites requiring a QM description 66 , and for which errors in relative free energies do not generally fall below 20 kJ/mol due to poor accounting of strong correlation using DFT 67 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…These enzymes, knowna sh ydrogenases, have catalytic efficiency that is unmatched by any manmadec atalyst. [6] 3. Unfortunately,d ue to their intricate architecture, there has not been ap recise agreement on how hydrogenases function.…”
Section: Her In Hydrogenasesmentioning
confidence: 99%
“…[4, 5b] For am ore in-depth analysis on theoretical methods involved in these studies, we refer the readert oa ne xcellent review by Vaissier and VanV oorhis. [6]…”
Section: Her In Hydrogenasesmentioning
confidence: 99%
See 2 more Smart Citations